An Analysis of Managerial Use and Market Consequences of Earnings Management and Expectation Management - Das, Somnath; Kim, Kyonghee; Patro, Sukesh (The Accounting Review, 2011)
ABSTRACT This study examines how managers coordinate the joint use of earnings management and expectation management by estimating the relationship between these instruments and how this relationship changes as their respective constraints change. We do this by estimating structural models of the two instruments that account for the constraints on their use as well as their effects on each other. Our results suggest that managers use earnings management and expectation management complementarily when managers' ability to use earnings management is less restricted. However, as the constraints on earnings management increase, managers substitute earnings management with expectation management. Moreover, we find that the extent of expectation management influences the extent of earnings management, but not vice versa. Examining the market consequences of the use of these instruments, we find that, while there are penalties for using both earnings management and expectation management, either as complements or as substitutes, the net stock price benefit from meeting or beating earnings targets exceeds these penalties. JEL Classifications: G14; M41. Data Availability: Data are available from public sources identified in the study.